Pengaplikasian dan Pengelolaan Aplikasi E-Lampid tingkat Kelurahan Genteng Surabaya - Ananda Utomo, Lydia Sevianti (Education and Talent Development Center of Indonesia, 2022)
Public services are all forms of services, both in the form of goods and public services provided by the government to fulfill public services. Public services provided by the government are of various kinds, one of which is population management. The Department of Population and Civil Registration of the city of Surabaya is one of the agencies that serve population management but there are still many problems and obstacles in its implementation. Therefore, the Surabaya City Government innovated population services, namely the E-Lampid Application. E-Lampid is a service for obtaining or managing Birth Certificates, Death Certificates, Transfer Letters online. The e-Lampid is distributed on the streets in Surabaya to ease the public in managing their documents. With the MBKM Dispendukcapil Internship activities, we get many benefits and expertise in public services and population administration. At the agency that I did in that place, namely the Genteng Exit with the aim of fulfilling public services, the rights of every citizen that must be fulfilled by the state's obligation to carry out a service. Basically, every human being needs service, both physical and non-physical, even in the extreme, service cannot be separated from human life. Population administration is one form of state service to its people, where as population administration it is an activity of structuring and controlling the issuance and population data through population registration, civil registration and management of population information as well as the utilization of results for public services, government and other sectors. To realize the public service itself, every information on population data plays an important role for the community itself. Therefore, we as Internship students at Dispendukcapil want to know how the population administration service is, especially in making birth certificates and family cards at the Population and Civil Registration Service in Genteng Village.